Postpartum Depression Leading to Suicidal Death – A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
During Post partum period up to 85 % of women experience some type of mood disturbance. For most women symptoms are transient and relatively mild. Sometimes women experience most disabling form of depression leading to suicide. The link between the reproductive status and depression illness is further evident by the high frequency of depression during the pre menstrual phase, the peri menopausal phase and the immediate post partum period. Post partum depres sion can lead to suicide because the women suffer from hopelessness and depression. The most telling post partum depression symptom usually involves crying, sadness, fatigue, and changes in sleeping and eating patterns, anxiety and irritability. Here we discuss such a case where a woman who was in post partum depression succumbed to death by committing suicide by hanging.
Keywords: Post Partum depression; suicide; hanging